Deterioração controlada em sementes de melancia - Soares, Lucas Carvalho (2021)
Vigor tests are essential to assess seed quality, in addition to providing reliable information for the management of seed lots. Thus, the objective of this work was to estimate the efficiency of the controlled deterioration test in determining the quality of seed lots of Watermelon (Citrullus lanatus (Thumb.) Matsum & Nakai). The experiment was carried out at the Seed Analysis Laboratory of the Federal University of Ceará (UFC), using four seed lots of the cultivar Crinson Sweet. The experiment was carried out in a completely randomized design, in a 4 x 2 x 2 x 2 factorial scheme (four lots, two temperatures, two seed moistures and two exposure times), with four replications. The initial characterization of the lots was carried out through germination tests, first germination count, accelerated aging, electrical conductivity, field emergence and emergence speed index. Seeds were adjusted to water content of 18% and 24% and then subjected to controlled deterioration in a water bath at temperatures of 41°C and 45°C for 48 and 72 hours. Data were subjected to analysis of variance and means compared by Tukey test at 5% probability. The simple linear correlation coefficients (r) between the result of the controlled deterioration test and the batch characterization tests were also calculated. The controlled deterioration test can be efficient to evaluate the quality of watermelon seed lots, where combinations with water content of 18%, associated with temperatures of 41°C or 45°C for 48 hours were the most efficient to verify the vigor of the lots of the studied species.